2013
DOI: 10.1371/journal.pone.0084202
|View full text |Cite
|
Sign up to set email alerts
|

3D Mapping of Safe and Danger Zones in the Maxilla and Mandible for the Placement of Intermaxillary Fixation Screws

Abstract: Intermaxillary (IMF) screws feature several advantages over other devices used for intermaxillary fixation, but using cone beam computed tomography (CBCT) scans to determine the safe and danger zones to place these devices for all patients can be expensive. This study aimed to determine the optimal interradicular and buccopalatal/buccolingual spaces for IMF screw placement in the maxilla and mandible. The CBCT volumetric data of 193 patients was used to generate transaxial slices between the second molar on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The regional distribution of root hits is contrary to the recommendations of CBCT‐based anatomical studies, which have declared safe and danger zones. For example, the spaces between the first and second premolars and between the second premolar and the first molar in the lower jaw are labelled as safe zones , whereas most injuries in the current study were found in this area (see Table ).…”
Section: Discussionmentioning
confidence: 88%
“…The regional distribution of root hits is contrary to the recommendations of CBCT‐based anatomical studies, which have declared safe and danger zones. For example, the spaces between the first and second premolars and between the second premolar and the first molar in the lower jaw are labelled as safe zones , whereas most injuries in the current study were found in this area (see Table ).…”
Section: Discussionmentioning
confidence: 88%
“…To correct minor discrepancies in occlusion, the arch bar was placed for 4 weeks to enable the postoperative traction. [ 9 10 ]…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…[ 11 ] At the time of arch bar removal, tooth vitality was checked using electronic pulp tester (Vitality Scanner™ 2006), a diagnostic tool traditionally used to determine the vitality of dental pulp preoperatively and postoperatively. [ 9 10 ] Oral hygiene was assessed using the Oral Hygiene Index-Simplified (OHI-S)[ 12 ] by examination of debris, stains, and calculus on specific surfaces of 6 index teeth that included the buccal and lingual surfaces of maxillary and mandibular molars and central incisors. [ 12 ] The Index values were calculated using the debris score and calculus score.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…The present study used CBCT imaging to measure the shortest distance between the mandibular canal and the surface of the mandible at various heights. Several previous studies of OAD placement sites used CT images (21)(22)(23)(24)(25), and a cadaveric study confirmed the accuracy of such images (6). However, CT imaging, including CBCT, is regarded as an invasive examination because of the radiation exposure involved.…”
Section: Discussionmentioning
confidence: 79%